Novel "After Minoxidil" spray improves topical minoxidil compliance and hair style manageability. (26th August 2020) - Kovacevic, Maja; McCoy, John; Shapiro, Jerry; Sinclair, Rodney; Vaño‐Galvan, Sergio; Goldust, Mohamad; Situm, Mirna; Goren, Andy
Abstract: Background: Topical minoxidil is the only US FDA‐approved drug for the treatment of female pattern hair loss (FPHL). While the safety profile of topical minoxidil is excellent, the efficacy of minoxidil in hair growth is extremely low. A recent survey of 8000 people observed that only 4% of hair loss patients using an over‐the‐counter minoxidil were very satisfied with their results. In contrast, in clinical studies with an intervening physician, approximately 30%‐40% of patients demonstrate an appreciable benefit. Compliance with topical drug regimens is often a major obstacle, limiting their effectiveness. Topical minoxidil leaves a greasy residue on the hair, which is especially problematic for women who do not wash their hair daily. Aims: We set out to develop an "After Minoxidil" companion spray to minoxidil that removes residual minoxidil from the hair, where it is not needed, yet leaves minoxidil on the scalp where it is required. We hypothesized that improving the cosmetic properties of minoxidil would improve patient compliance with the drug and subsequently improve clinical outcomes. Methods: A cohort of 20 FPHL patients was recruited to use the novel "After Minoxidil" spray and report changes in hair quality on a Likert scale. Results: In our cohort of FPHL patients, the novel "After Minoxidil" spray restored ease of styling and reduced greasiness to preminoxidil level in 65% and 85% of subjects, respectively. The average reduction in perceived greasiness was 78%. Importantly, 70% of subjects interviewed stated they would likely continue to use the minoxidil and "After Minoxidil" treatment regimen for 6 months, vs 0% willing to use minoxidil alone. Conclusion: The novel "After Minoxidil" spray improved ease of hair styling and reduced greasiness following application of topical minoxidil; thus, the novel "After Minoxidil" spray may help improve drug compliance and efficacy.